Los Baños folk festival its role in sustaining health of the socio-cultural environment - Buot, Merites M. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2008)
Sustaining the health of man's environment demands nurturing its various components including the complex socio-cultural practices like traditions and festivities, among others. The Filipinos love festivities. These are always associated with sumptuous food preparation and worship to a patron saint. Devotees have their own personal intentions in observing festivals and usually it is the panata, a religious vow that drives namamanata (devotee) to do physical sacrifices just to attain it. The Elejer (Elijer) folk festival of Barangay Anos, at the foot of Mt. Makiling and Barangay Mayondon, along the coast of Laguna Lake was investigated to determine its role in sustaining health of the socio-cultural environment. The case study method using key informant interview (KII) among nine namamanata was done. Elejer enhances cohesiveness/unity, cooperation and place identity among participants. Renewed vigor both physically and psychologically as experienced by the namamanata sustains a healthy socio-cultural environment contributing to overall environmental health of the families and the localities concerned.